(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
The ability to comprehend and apply information from a variety of electronically obtained formats is recognized as digital literacy, and it can result in a more comprehensive and global understanding of the world. Researchers employed descriptive qualitative research using the listening method, skill method, and introspection method to describe how digitalization affected early childhood language development and cultural interests. There is a negative effect on language development on oral communication skills because it directly diminishes their social interactions, in spite of the results indicating an increase in language skills and multilingual abilities and also changes in language patterns. Understanding about both local and global cultures, creating an appreciation for traditional cultures, and enhancing creativity in ways that express culture are all factors that influence cultural interest. However, because they are more interested in foreign cultures, native cultures are also at threat. Thus, in order to cultivate cultural interest in young children, researchers suggest that language development be balanced by utilizing the mother tongue in the family circumstance. In addition, it is an ancestral heritage that embodies traditions, values, and history.